Cause analysis of the liner dissociation of a customized reverse shoulder prosthesis based on finite element analysis - Wan, Qian; Zhang, Aobo; Bai, Haotian; Liu, Yang; Chen, Hao; Zhao, Xin; Wang, Xiaonan; Han, Qing; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Dissociation of the polyethylene liner after reverse shoulder arthroplasty could cause shoulder dislocation that could not achieve closed reduction. The cause of liner dissociation is currently unclear. Method: Non-homogeneous model of the bone was constructed and dynamic finite element analysis was utilized to simulate the impingement of the polyethylene liner and scapula during humeral adduction. The stress distribution of the fixation claws, their degree of deformation (DOD), and the stress of the impingement sites in three initial humeral postures (neutral, 30° flexion, and 30° extension) were measured and analyzed. The influence of the liner material stiffness was also investigated. Result: The impingement stress on the liner and scapula was 100 to 200 MPa, and different humeral postures caused different locations of impingement points. The fixation claws’ maximum principal stress (MPS) results were below 5 MPa. In the connection area between some fixation claws and the liner, compressive stresses on the inside and tensile stresses on the outside were observed, which showed that the fixation claws were prone to deform toward the center direction. The maximum DOD results of three initial humeral postures (neutral, 30° flexion, and 30° extension) were 3.6%, 2.8%, and 3.5%, respectively. The maximum DOD results were 0.51% and 11.4% when the elastic modulus of the liner was increased and decreased by a factor of 10, respectively. Conclusion: The humeral adduction impingement could lead to the deformation of the liner fixation structure, which might be one of the reasons for the liner dissociation. The increased stiffness of the liner material helped to reduce the deformation of the fixation structure.